Integration of value stream map and strategic layout planning into DMAIC approach to improve carpeting process - Ayman Nagi; Safwan Altarazi (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: This paper presents an implementation of the Six Sigma DMAIC approach implementing lean tools and facilities layout techniques to reduce the occurrence of different types of nonconformities in the carpeting process. Such carpeting process can be found in several industries such as construction, aviation, and automotive. Design/methodology/approach: The improvement process was built through a sequential implementation of appropriate interconnected tools at each phase of the DMAIC approach. Utilized tools included: Pareto analysis, control charts, Ishikawa chart, 5-whys, failure mode and effect analysis, process capability ratio, value stream mapping, and strategic layout planning. Findings: The carpeting process capability, quality of the product, customer satisfaction, and cost of poor quality were significantly improved. Explicitly, the sigma level was improved from 2.297 to 2.886 and the defects per million opportunities (DPMO) was reduced from 21615 to 3905. Originality/value: This paper has approved the capability of the Six Sigma DMAIC approach to analyze, investigate, and remove the root causes of the carpeting (preparation-installation) process nonconformities .
Keywords: 650; carpeting process; define-measure-analyze-improve-control (DMAIC) approach; process improvement; statistical process control; value stream mapping; and facilities planning